2021
DOI: 10.3399/bjgp.2020.1101
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative improvement in Scottish GP clusters after the Quality and Outcomes Framework: a qualitative study

Abstract: Background: Scotland abolished the Quality and Outcomes Framework (QOF) in April 2016, prior to implementing a new Scottish GP contract in April 2018. Since 2016, groups of practices (GP clusters) have been incentivised to meet regularly, to plan and organise quality improvement (QI) as part of this new direction in primary care policy. Aim: To understand the organisation and perceived impact of GP clusters, including how they use quantitative data for improvement. Design/Setting/Methods: Thematic analysis, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Our findings on the continuing slow progress on cluster working is consistent with our previous research [12,13] and with a newly published report by Healthcare Improvement Scotland [22]. Indeed, concerns raised in a high-level workshop organised by the SSPC in 2016, that poor infrastructure support would be a barrier to effective cluster working, appear to have been borne out [23].…”
Section: Relationship With Published Literaturesupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings on the continuing slow progress on cluster working is consistent with our previous research [12,13] and with a newly published report by Healthcare Improvement Scotland [22]. Indeed, concerns raised in a high-level workshop organised by the SSPC in 2016, that poor infrastructure support would be a barrier to effective cluster working, appear to have been borne out [23].…”
Section: Relationship With Published Literaturesupporting
confidence: 90%
“…There has been no published evaluation of the expansion of the MDT in Scotland. A national survey of GP clusters in Scotland conducted in 2018 by the Scottish School of Primary Care (SSPC) found that whilst clusters were "up and running", there was a perceived general lack of structural support, training and capacity building [12], which was supported by subsequent qualitative interviews with a range of different stakeholders [13]. The aim of the present study was to investigate the views of key national primary care stakeholders (PCSs) and CQLs working in three different Health Board areas of Scotland (high deprivation, mixed/affluent, remote and rural) on the GP contract and wider primary care reforms.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding that QCs should be embedded in a system of QI that values, integrates and uses new external knowledge aligns with the existing literature 22 23. Health systems should provide training in QI tools and give access to trustworthy data (explicit knowledge) that help participants identify their own learning needs (CMO configuration 1 b-c and 3 e in figure 2 24–28…”
Section: Discussionmentioning
confidence: 69%
“…23 46 Health systems should provide training in QI tools and give access to trustworthy data (explicit knowledge) that help participants identify their own learning needs (CMO configuration 1 b-c and 3 e in Figure 2). 22 47-50…”
Section: Discussionmentioning
confidence: 99%